2018
DOI: 10.1111/agec.12449
|View full text |Cite
|
Sign up to set email alerts
|

Are maize marketers averse to quality loss in supplies? A case study from Ghana

Abstract: To ensure sustainable post-harvest loss reduction, markets that are averse to quality loss and provide incentives for farmers to supply high quality produce are crucial. Such markets will be averse to quality loss, offering distinct prices and substantial rewards to farmers for the supply of quality produce. Farmers in sub-Saharan Africa (SSA), where informal markets exist, have often assessed the rewards for the supply of quality produce as inadequate. Hence, this study investigates if intermediary buyers are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Food hazard information is assumed to be a valuable food safety resource for cowpea consumers and can enable them to make better purchase and consumption decisions in the bid to reduce their exposure to the hazard. Based on the theory of risk aversion and the principle of expected utility maximization, concepts from Goldberg and Roosen (2007) and Bassey et al (2018) are adapted and modified to derive a framework for assessing consumers' aversion to risks associated with cowpea storage after receiving hazard information. Consumers response to the hazard information were considered for two types of risks -that of buying cowpea stored with unsafe pesticide (purchase risk) and the health risk associated with consuming cowpea stored with unsafe pesticides (consumption risk).…”
Section: Conceptual Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Food hazard information is assumed to be a valuable food safety resource for cowpea consumers and can enable them to make better purchase and consumption decisions in the bid to reduce their exposure to the hazard. Based on the theory of risk aversion and the principle of expected utility maximization, concepts from Goldberg and Roosen (2007) and Bassey et al (2018) are adapted and modified to derive a framework for assessing consumers' aversion to risks associated with cowpea storage after receiving hazard information. Consumers response to the hazard information were considered for two types of risks -that of buying cowpea stored with unsafe pesticide (purchase risk) and the health risk associated with consuming cowpea stored with unsafe pesticides (consumption risk).…”
Section: Conceptual Approachmentioning
confidence: 99%
“…The amount of c is such that in the worst case, the consumer is indifferent between when his expected utility is as given in equation 1 and when it is as given in equation 2. A payment for risk reduction or elimination, such as c, is a function of the extent of risk reduction expected (Bassey et al, 2018). Goldberg and Roosen (2007) showed that such a cost c is increasing in the risk reduction (r − ro).…”
Section: Aversion To Purchase Risk Associated With the Use Of Unsafe ...mentioning
confidence: 99%
“…Private investments in maize and wheat sectors are emerging but with a main focus on domestic markets (eg, for local breweries, animal feed, or other food processing industries). Cereal supply chains are often inefficient with a lack of coordination along the chain and mainly spot market exchange, substantial postharvest losses, and low quality (Bassey, Kuhn, & Storm, ; Daly, Hamrick, Gereffi, & Guinn, ). In Zambia, an important regional maize supplier, maize is increasingly produced by medium‐scale farmers (along‐side large‐scale commercial farms), resulting in tradable surpluses and entry of multinational grain trading companies (Jayne et al., ; Sitko, Burke, & Jayne, ; Sitko, Chisanga, Tschirley, & Jayne, ).…”
Section: Introductionmentioning
confidence: 99%